Correlation analysis of the Causes of College Teachers' Professional Psychological Pressures - Li Ting, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In modern times, due to the rapid significance given to learning outcomes, colleges and universities in China have set higher standards for the eligibility and recruitment of university teachers. The increasing teaching workload, mandatory research publications, low or inefficient school administration, stringent promotion regulations, and low salary are a few pressures on university teachers who already endure huge pressures of work, family, and society. This research study is an attempt to deal with these pressures and attempt a solution. Questionnaires were used to investigate teachers who were 40 years age and below in a Chinese university. Findings show that teachers' professional psychological stress in a university has significant differences in gender, age, marriage, teaching age, subject category, monthly salary level, and a number of children. Multiple regression analysis shows that role responsibilities, job security, and interpersonal relationships have significant predictive effects on college teachers' psychological response and physiology. Likewise, role responsibilities, job security, and scientific research have substantial predictive effects on college teachers' behavioral responses. This research also put forward relief measures for college teachers' professional psychology by constructing a people-oriented school management system, establishing an effective promotion evaluation system, establishing a fair and reasonable salary level and distribution system, and teachers themselves should learn to manage professional psychological pressure.